Determinants of Passive Smoking Behavior in State Elementary School Children 59/IV in Jambi City in 2024 - Yusril Ihza Mahendra; Ismi Nurwaqiah Ibnu; Muhammad Rifki Azhari; La Ode Reskiaddin (Lembaga Pengembangan Kinerja Dosen, 2025)
Background : Smoking is a dangerous habit that causes various diseases and death. Passive smokers, especially children and teenagers, are more susceptible to disease than active smokers. The prevalence of passive smoking in Indonesia is quite high, especially among women (66%) and teenagers (12.7%). Jambi Province has a high number of active smokers (27.47%), resulting in an increase in passive smoking among children and teenagers. Therefore, this study aims to analyze the factors that influence passive smoking behavior among elementary school children in Jambi Province. Methods : This research uses quantitative methods with an analytical observational design. The design of this research is cross-sectional, where each subject is only observed once. Data collection was carried out through approaches, observations and data collection simultaneously on students at Elementary School 59/IV, Jambi City. Results : The results showed that 9 respondents (13.8%) were passive smokers, while 56 respondents (86.2%) did not smoke passively. Statistical analysis found a significant relationship between knowledge and attitudes and passive smoking behavior (p < 0.05). However, the influence of peers and family did not have a significant relationship. Conclusion : This research concludes that increasing knowledge and positive attitudes can reduce the risk of passive smoking behavior in elementary school children. Therefore, prevention programs should focus on health education and the formation of positive attitudes.